Implementasi Peraturan Gubernur DKI Jakarta Nomor 77 Tahun 2020 tentang Pengelolaan Sampah Dalam Meningkatkan Kualitas Lingkungan di RW 015 Kelurahan Duren Sawit, Kota Administrasi Jakarta Timur. - Fitri Heri Kustanti; Hery Chariansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Discussing public awareness of the environment they live in recently can be said to be worrying, but this situation does not occur in the RW.015 Duren Sawit Village environment. This is an interesting topic to discuss, how this could happen, while there are some people who no longer believe that there are villages where the community still plays an active role. What factors exist to create an environment that they call